Investigating on Verbal Views of Asharites and Mutazilite on Quality of Divine Kalam - Mohammadreza Hajiesmaeili (Comparative Theology, 2010)
According to one of the historical reports, the of knowledge of Kalam is started with question about the quality of divine Kalam and this knowledge is called with this name when some of Muslim thinkers emphasized the creation of Divine Kalam and some others the ancientness of that. Some groups allowed the title of prolocutor to God's essence and some others who considered the nature of word the combination of Phonemes and letters, didn’t allow the attribution of this trait to God because acceptance of this believe necessitates that God exposed to events and so signs of possibilities affected his majesty. This Study tries to investigate and ingeminate the quality of Divine Kalam based on two verbal views of Asharites and Mutazilites, then with a brief references to some of Imam's word and by mentioning two points that universe is the word of God and word of God has hierarchies, explains this notion.